MULTIPERSPECTIVE REVIEW OF FAMILY PEDAGOGY AS A SCIENCE (American Journal of Research in Humanities and Social Sciences, 2024)
Family and society are a mutually integrated process. Development based on the content, ideas and principles of education, which is organized in its important link as the basis of renewed development, is the demand of the times. Therefore, in the current conditions, which is a new period in the historical development of Uzbekistan, it is necessary to decide on a new approach to the issue of raising children in the family. Therefore, the objective of this paper is to analyze past reviews and gain deeper knowledge of science of family pedagogy on multiple viewpoints.